Japan`s response to the Covid-19 pandemic: A cautious and self-restraint-based approach - Suzuki, K.; Sakuwa, K. (International Comparative Analysis of COVID-19 responses, 2021)
This chapter explores how Japan responded to and mitigated the spread of COVID-19. The COVID-19 pandemic has posed unprecedented challenges to policy makers all over the world. The coronavirus pandemic can be understood as a wicked problem for policy makers (Ansell, Sørensen, and Torfing 2020, Steen and Brandsen 2020, van den Oord et al. 2020), characterized by "unclear problem definitions, complex causalities, conflicting goals and lack of standard solutions" (Ansell, Sørensen, and Torfing 2020, 2). As Moon (2020) argues, the Covid-19 outbreak has tested governments` abilities to solve wicked policy problems; in particular, governments have faced new challenges in preparing for, mitigating, and responding to the threats posed by contagious disease. It is noteworthy to observe the significant variations in how governments have responded to and handled these unprecedented policy challenges. Some countries seem to have managed the COVID-19 crisis more effectively and swiftly than others in terms of several infection-related indicators (Van der Wal 2020). Although it is premature to draw any conclusions at this point, some countries—especially those in the Asia Pacific region, including South Korea, Taiwan, New Zealand, Australia, and possibly Singapore—seem to have controlled coronavirus more effectively than other countries (An and Tang 2020, Bromfield and McConnell 2020, Dunlop, Ongaro, and Baker 2020, Huang 2020, Jamieson 2020, Moon 2020, Van der Wal 2020).